2013
DOI: 10.1007/s40062-013-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

BP: close encounters of the $$E_\infty $$ E ∞ kind

Abstract: Inspired by Stewart Priddy's cellular model for the p-local Brown-Peterson spectrum BP , we give a construction of a p-local E∞ ring spectrum R which is a close approximation to BP . Indeed we can show that if BP admits an E∞ structure then these are weakly equivalent as E∞ ring spectra. Our inductive cellular construction makes use of power operations on homotopy groups to define homotopy classes which are then killed by attaching E∞ cells.Date: 29/07/2013 version 6 (to appear in Journal of Homotopy and Relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The result agrees completely with previously obtained results as well as actual cosmological measurements and observations [30]. The mathematical basis of the present analysis is rooted in the theoretical structure of E-infinity theory of highly structured rings [12] [13] of which E-infinity theory of high energy physics and loop quantum gravity are in the meantime two well known applications. This was accomplished in part by integrating number theory, the queen of mathematical science and consequently of science in physics [10].…”
Section: Resultssupporting
confidence: 90%
“…The result agrees completely with previously obtained results as well as actual cosmological measurements and observations [30]. The mathematical basis of the present analysis is rooted in the theoretical structure of E-infinity theory of highly structured rings [12] [13] of which E-infinity theory of high energy physics and loop quantum gravity are in the meantime two well known applications. This was accomplished in part by integrating number theory, the queen of mathematical science and consequently of science in physics [10].…”
Section: Resultssupporting
confidence: 90%
“…We will show that the T (n) arise quite naturally as skeleta of BP as an associative algebra, and that the necessary cells are detected by topological Hochschild homology with coefficients. (Cellular constructions, in various categories, of objects related to BP are by no means new: see, for example, work of Priddy [Pri80], Hu-Kriz-May [HKM01], or Baker [Bak14].) By similar methods, it is also possible to show that the 2-primary spectra Y (n) of Mahowald-Ravenel-Shick [MRS01] arise as skeleta of the Eilenberg-Mac Lane spectrum for F 2 , although this can be shown more directly using their construction as Thom spectra.…”
Section: Main Applicationsmentioning
confidence: 99%
“…More recently Basterra-Mandell showed that BP is a split summand of MU (p) as an E 4 -algebra [BM13], and so the homotopy category of BP-modules has a symmetric monoidal structure; Chadwick-Mandell used idempotent splittings to show that this could be done with the Quillen idempotent as E 2 -algebras [CM15]. Both Hu-Kriz-May [HKM01] and Baker [Bak14] gave iterative constructions by methods that kill torsion, producing two different types of closest possible torsion-free E ∞ -algebra to BP. An unpublished paper of Kriz attempted to prove that BP admits an E ∞ -algebra structure, and Basterra developed the theory of topological André-Quillen (TAQ) cohomology based on his ideas-this theory allows the construction of E ∞ -algebras by systematically lifting the k-invariants in the Postnikov tower from ordinary cohomology to TAQ-cohomology [Kri95,Bas99].…”
Section: Introductionmentioning
confidence: 99%